Evolving Therapeutic Landscape of ROS1-Positive Non-Small Cell Lung Cancer: An Updated Review - Bischoff, Hervé; Gendarme, Sébastien; Somme, Laura; Chouaid, Christos; Schott, Roland (Current oncology (Toronto), 2025)
ROS1 gene rearrangements define a distinct molecular subtype of non-small cell lung cancer (NSCLC), occurring in approximately 2% of cases and frequently associated with younger age, non-smoker status, and a high incidence of brain metastases. The discovery of ROS1 as an oncogenic driver has led to the development of targeted tyrosine kinase inhibitors (TKIs). Crizotinib first demonstrated substantial clinical benefit, but its limitations, including poor central nervous system (CNS) penetration and acquired resistance, highlighted the need for next-generation inhibitors. Several agents have since been developed, including entrectinib, lorlatinib, repotrectinib, taletrectinib, and zidesamtinib, each offering improved intracranial (IC) activity and efficacy against resistance mutations, notably ROS1^G2032R. Despite these advances, optimal sequencing strategies remain undefined, and resistance ultimately emerges in most patients. This review provides an updated overview of ROS1 biology, diagnostic approaches, clinical outcomes with currently available TKIs, mechanisms of resistance, and ongoing challenges, emphasizing the rapidly evolving therapeutic landscape.